Fall prediction using a wearable conductive fabric - Kwek, Cherilyn Le Qi (Nanyang Technological University, 2024)
Our human joint mobility is vital to perform many activities of daily (ADL) needs, and any reduction in the range of motion (ROM) on the joint could have hinted at some form of lesions within the limb. Hence gathering reliable and precise data of the joint function over an extended period is imperative for clinical assessment. However, most of these measurement approaches utilized either non-wearable systems (NWS) or wearable systems (WS) that are too rigid and interfere with limb movement. Therefore, there is a need to look at a new breed of WS measurement devices that the user can wear and track their kinematic data without interfering with the limb motion. Over the past decade, conductive fabrics (CF), has evolved as an emerging trend to measure kinematic parameters due to their comfort & soft property.